Unravelling intra-party democracy in Thailand - Croissant, Aurel; Chambers, Paul W. (Asian journal of political science, 2010)
This survey aims to analyze the state of intra-party democracy (IPD) in Thailand. IPD is defined as a characteristic of the distribution of decision-making power among members and leaders within a political party along the two principal dimensions of inclusiveness and decentralization. The amount of organizational details that could be used to describe parties' procedures with regard to all aspects of their internal life is placed into three generalizable categories: candidate selection, setting party policies, and coalition formation procedures. In addition, this survey provides some background on the territorial spread, membership developments and funding practices of political parties. The overall finding is that the degree of internal democracy of political parties in Thailand is quite limited. Thai political parties tend to be ‘electoral parties’ with weak organizations, low policy capacity and vague ideologies. The development of political parties since 1997 (and before the 2006 coup) can best be described as a process of party centralization without institutionalization. This has produced significant consequences for the realization of internal democracy within political parties: weak internal organization decision-making remains largely informal and is controlled by a limited number of party elites. This general result has important implications regarding the prospects of party politics in Thailand and democratic consolidation.
Gesehen am 23.03.2021